2018
DOI: 10.2144/btn-2017-0104
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nucleic Acids with a Novel Stem-Loop Primer Rolling Circle Amplification Technique

Abstract: This paper presents a new rolling circle amplification (RCA) technique using stem-loop primers (SLP). The technique enables detection of target DNA by either linear or exponential amplification (SLP-lRCA and SLP-eRCA) in both liquid and solid phases. For solid-phase detection, SLP-eRCA detects nucleic acids in four steps: (1) covalently immobilize an array of capture probes (CP) on a solid support; (2) hybridize the CP array with the DNA sample; (3) incubate the CP array with an RCA reaction containing two SLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…RCA designed with stem-loop primer has been used to detect HPV16 and HPV18 from carcinoma cells of the cervix, and cervical mucus exfoliated cell samples. 128 Similarly, H5N1 influenza virus detection using hyperbranched RCA with a detection limit of 9fM has been reported. 122 The authors reported that results obtained by RCA compared favourably to standard real-time PCR.…”
Section: Dovepressmentioning
confidence: 84%
See 1 more Smart Citation
“…RCA designed with stem-loop primer has been used to detect HPV16 and HPV18 from carcinoma cells of the cervix, and cervical mucus exfoliated cell samples. 128 Similarly, H5N1 influenza virus detection using hyperbranched RCA with a detection limit of 9fM has been reported. 122 The authors reported that results obtained by RCA compared favourably to standard real-time PCR.…”
Section: Dovepressmentioning
confidence: 84%
“…RCA products can be detected using gel electrophoresis [120][121][122] or visually using fluorescence spectroscopy, microscopy and flow cytometry. [123][124][125][126][127] Furthermore, incorporating nanoparticles such as gold nanoparticles (AuNPs), magnetic beads, and quantum dots into RCA products [128][129][130] can aid the visualisation of products. Primers designed for PCR can be used for RCA.…”
Section: Dovepressmentioning
confidence: 99%
“…Typically, in a circle-to-circle amplification process, amplicons of the first round RCA will be converted into multiple circles by monomerization (endonuclease digestion) and ligation. Subsequently, newly formed circles will act as templates for the following round RCA, thus reaching an ultra-low limit of detection [ 97 ]. To further improve the efficiency of amplification, some exponential or quadratic amplification formats are developed and combined with RCA-based approaches.…”
Section: Detection Mechanism Of Sars-cov-2mentioning
confidence: 99%
“…Because of the multiple tandem-repetitive units, we have built large-scale nanostructures using RCA as scaffolds and developed salt-induced assembly transformation of DNA–AuNP conjugates based on RCA. Moreover, RCA possesses the significant advantages such as simple design, high sensitivity, high selectivity, high throughput, easy operability, and so on. Hence, RCA-amplified ssDNA has been widely used for signal amplification for sensitive detection of micro-RNA, transcription factors, virus, enzymes, and circulating tumor cells. According to the literature reports, RCA triggering the fluorescence of MB is becoming a new research focus in the field of analysis and detection. The RCA scaffolds hybridize tens or hundreds of aptamer-modified MBs to form polyvalent aptamer probes, which can be used to design a cascade signal amplification strategy for ultrasensitive and high specific determination of target cells through targeting agents.…”
Section: Introductionmentioning
confidence: 99%